PortaCredit: improving microloan processing - Gutiérrez, Laurie (Technical Centre for Agricultural and Rural Cooperation, 2003)
Laurie Gutierrez reports from Ecuador where loan officers from a local microfinance institution are using hand-held computers to speed up the processing of microloan applications.